1992
DOI: 10.1111/j.1365-2796.1992.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of smokeless tobacco: blood pressure elevation and other health hazards found in a large‐scale population survey

Abstract: Health hazards associated with the use of smokeless tobacco were evaluated in a cross-sectional study of 97,586 Swedish construction workers undergoing health examinations in 1971-74. All users of smokeless tobacco only (5014 subjects) and all exclusive smokers of > or = 15 cigarettes daily (8823 subjects) were compared with all non-users of any tobacco (23,885). Both smokeless tobacco users and smokers showed higher prevalences of circulatory and respiratory disorders. Hypertension was most common in smokeles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
89
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 23 publications
12
89
2
Order By: Relevance
“…It is also pertinent to note that this study demonstrated a significantly increased risk of hypertension among current smokers with smoking intensities as low as just over four cigarettes per day, compared to those who had never smoked. However, in contrast to findings from previous studies, 7,8 this study failed to show a significant independent association between the use of snuff and hypertension. The difference in this observation may be related to the differences in snuff products and additives used in the different countries and/or the differences in the socio-demographic characteristics of the study populations.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It is also pertinent to note that this study demonstrated a significantly increased risk of hypertension among current smokers with smoking intensities as low as just over four cigarettes per day, compared to those who had never smoked. However, in contrast to findings from previous studies, 7,8 this study failed to show a significant independent association between the use of snuff and hypertension. The difference in this observation may be related to the differences in snuff products and additives used in the different countries and/or the differences in the socio-demographic characteristics of the study populations.…”
Section: Discussioncontrasting
confidence: 56%
“…Some studies have shown that the use of oral snuff or smokeless tobacco may predispose a person to higher systolic and diastolic blood pressures, 5,6,7 and significantly increase the risk for myocardial infarction. 8 A few studies have also suggested an acute elevation of blood pressure following snuff-dipping, ascribed to the mineralocorticoid activities of nicotine, the high sodium content and possibly the effect of liquorice additives.…”
Section: Introductionmentioning
confidence: 99%
“…26 Two large studies in the US and Sweden have reported no or a positive relationship between smokeless tobacco use and blood pressure in men. 27,28 These divergent results may reflect differences in the effect of snuff in these populations or in other unmeasured characteristics associated with snuff use in Zimbabwean women. Although they reached statistical significance, risk factors other than age and BMI (or other related anthropometric measures) explained little of the variation in SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cardiovascular effects of chewable tobacco are similar to those of cigarette smoking, 8,9 but the age adjusted relative risk of dying from CVD is lower with smokeless tobacco than tobacco smoking. 10 We combined cigarette smoking and any form of tobacco use together because reporting only cigarettes smoking would under report the use tobacco in this society.…”
mentioning
confidence: 99%